Da efetividade da mediação familiar: uma análise da atuação do CEJUSC da comarca de Uberlândia no período de julho/2016 a maio/2018 - Ricardo, Laura Borges (2020)
This study consists of an analysis of the effectiveness of mediation in family causes, at the Judicial Center for Conflict Resolution of the district of Uberlândia, from July/ 2016 to May/ 2018. Thus, we intend to investigate the following issues, as pre-procedural mediation is a means of conflict resolution that contributes to the efficiency of the Judiciary? And does procedural mediation make civil proceedings effective? Statistical data show that both pre-procedural and procedural mediations in the family area stand out as excellent forms of consensual dispute settlement, by ensuring the effectiveness of the proceedings and the efficiency of the Judiciary. The research is based on Kazuo Watanabe's analysis of access to justice, since the definition of accessibility to justice must be broader than access to action in order to find the solution to the dispute. The studies by Ada Pelegrini Grinover, Antonio Carlos de Araujo Cintra, and Cândido Rangel Dinamarco expose the guarantee of access to justice by any adequate means of conflict resolution; either by mediation or by conciliation. This dissertation uses the inductive approach method, the structuralist, functionalist and statistical procedure. It is also worth mentioning the use of the indirect documentation technique, which occurs, through bibliographic and doctrinal research, about the theoretical concepts and paradigms that underlie the fundamental right of access to justice, as well as the technique of direct documentation through intensive, systematic direct observation, when conducting interviews at CEJUSC of Uberlândia, and thus characterized as field research, collecting and interpreting statistical data from pre-procedural and procedural mediations, as well as to understand the structure and functioning of this body.